The Lithuanian students‘ opinion concerning innovative behaviour and its correlation with the KAI test scores - Almonaitienė, Junona; Lekavičienė, Rosita (Psichologija, 2002)
The investigation (2001) of the possibility to measure individual differences in creativity, problem solving and decision-making using the Kirton Adaption-Innovation Inventory (KAI) showed that the mean score of the Lithuanian university students' sample was significantly lower than the general population mean scores in some other countries (UK, USA, Slovakia, etc.). Thus, the Lithuanian students were found to be more adaptive. The current study examined the possibility that the opinion concerning innovative behavior could cause such results. To check it 228 university students were asked to complete the test and to refer what kind of behavior was most useful for them up to now at school, in the university, at work and while trying to raise some money, and which they expect to be most useful in their future carrier. 70.6 percent of all the behavior examples named by respondents represented the adaptive behavior. Such qualities as being a steady plodder, thorough and patient were, and would be, according to them, most useful in various fields of activity. The innovative behavior was said to be most appropriate while trying to raise some money (41.7 percent of the mentioned behavior examples), but much less appropriate at school, university, or work (only 25.1, 28.5 and 17.7 percent accordingly). A significant correlation was found between the KAI score and the preferred innovative (r = 0.692, p < 0.01) or adaptive (r = -0.554, p < 0.01) behavior examples. As hypothesized, the KAI scores can be related to attitude, prior experience, and, thus, the social cultural environment on the whole.
Keywords: innovative behaviour; KAI test